Nanosheets of Ni‐SAPO‐34 Molecular Sieve for Selective Oxidation of Cyclohexanone to Adipic Acid. Issue 38 (25th May 2022) - She, Minyi; Gu, Rongtian; Meng, Deming; Yang, Hua; Wen, Yujie; Qian, Xiaofeng; Guo, Xiangke; Ding, Weiping
Abstract: Nanosheets of nickel doped SAPO‐34 molecular sieves in thickness of ∼10 nm (denoted as NS−Ni‐SAPO‐34) has been successfully prepared through a morphology‐reserved method of synthesis. A special aluminum phosphate in two‐dimensional layered structure is used as precursor and converts to crystallized SAPO‐34 molecular sieve, in nanosheet morphology reserved from the aluminum phosphate precursor, under hydrothermal conditions with tetraethyl orthosilicate and templates of mixed amines added. It is found that adequate amount of nickel, ∼5 wt %, added to the synthetic system is a key factor for the morphology‐reserved synthesis. By characterization, the nickel is proved to be doped in the framework of the molecular sieve, which more likely helps to balance the high surface energy of nanosheet products. The NS−Ni‐SAPO‐34 shows excellent catalytic performance for oxidation of cyclohexanone to adipic acid by gaseous oxygen. Abstract : The Ni‐SAPO‐34 nanosheets have been prepared through introduction of Ni and Si into the artificial layered AlPO4 followed by exfoliation and crystallization process. The nanosheets has the 2D morphology reserved from layered precursors and the framework incorporated nickel stabilize the 2D structure, along with an extraordinary catalytic performance for the selective oxidation of cyclohexanone to adipic acid with O2 .